What did you eat yesterday? 09 - Yoshinaga, Fumi, 1971- (Vertical, 2015)
A hard-working middle-aged gay couple in Tokyo come to enjoy the finer moments of life through food. After long days at work, either in the law firm or the hair salon, Shiro and Kenji will always have down time together by the dinner table, where they can discuss their troubles, thrash out their feelings and enjoy delicately prepared home cooked meals! Intrepid lawyer/gourmand, shiro, deals with the closing of his beloved local supermarket, his ageing parents (and growing older himself), dodges lawyerly politics, and reveals a shocking secret to Kenji about why their apartment is so cheap to rent. Shiro continues to showcase an array of inventive, yet simple-to-make, dishes, and his cooking buddy Kayoko comes up with tasty recipes to cook up Mr. Kohinata's food after his fridge breaks down. The recipes include celebratory year-end-only dishes, as Shiro rings in the New Year at home, with Kenji, for the first time.